Voices of resistance : oral histories of Moroccan women - Baker, Alison, 1939- (SUNY series in oral and public history., 1998)
"Providing new information on women's participation in the Moroccan independence movement, Voices of Resistance offers a rare opportunity to hear Moroccan women speak freely about their personal lives. Each woman is introduced in terms of her family background and personal style, and the interviews are given texture and context by references to Moroccan history and popular culture, including contemporary songs and poems. These women are storytellers, and they lived through stirring times. Their active struggle against French colonialism also challenged and redefined traditional Moroccan ideas about women's roles in society. The narratives reconstruct the little-known history of Moroccan feminism and nationalism, and probe the lives of a remarkable group of Islamic women whose voices have never been heard until now."--Jacket